Building a Social Media Marketing Plan for Alibaba Media Company's Communication Services, Da Nang Branch - Vo, Thi Thu Hien (Vietnam-Korea University of Information and Communication Technology, 2025)
Bachelor thesis of Business Administration - Digital Marketing; 2021-2025.